1997
DOI: 10.1111/j.1600-051x.1997.tb01191.x
|View full text |Cite
|
Sign up to set email alerts
|

A study to investigate the effect of a propolis‐containing mouthrinse on the inhibition of de novo plaque formation

Abstract: The results of a study to investigate the effectiveness of a propolis-containing mouthrinse in the inhibition of de novo plaque formation are presented. Subjects used a propolis-containing rinse, a negative control and a positive control in a double-blind, parallel, de novo plaque formation study design. The chlorhexidine mouthrinse was significantly better than the others in plaque inhibition. The propolis-containing rinse was marginally better than the negative control, but this difference was not significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 11 publications
(8 reference statements)
5
50
0
5
Order By: Relevance
“…The experimental mouthrinse showed significant reduction of dental plaque compared to the placebo and also significant inhibition of IP formation. Recently, Murray et al [1997] found that a mouthrinse containing 10% propolis had no significant effect on dental plaque regrowth although a slight reduction (14%) was observed. The apparent contradiction with the present data may be explained by the high variability of the chemical composition and cariostatic properties of propolis.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental mouthrinse showed significant reduction of dental plaque compared to the placebo and also significant inhibition of IP formation. Recently, Murray et al [1997] found that a mouthrinse containing 10% propolis had no significant effect on dental plaque regrowth although a slight reduction (14%) was observed. The apparent contradiction with the present data may be explained by the high variability of the chemical composition and cariostatic properties of propolis.…”
Section: Discussionmentioning
confidence: 99%
“…Dodwad and Kukreja (2011) designed a single-blind parallel study to ensure that subjects were assigned randomly. In the third study conducted by Murray et al, participants were randomly assigned to either the experimental or control group and were blinded to treatment allocation (Murray et al, 1997). In the fourth RCT (Samet et al, 2007), participant assignments were randomized to receive either the propolis or the placebo.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
“…Muray ve ark. 46 %10 propolis gargarasının dental plak oluşumunu belirgin azalttığını tespit etmişlerdir.…”
Section: Propolis Ve Diş Hekimliğiunclassified